Ultrasound-assisted deep eutectic solvent as green and efficient media combined with functionalized magnetic multi-walled carbon nanotubes as solid-phase extraction to determine pesticide residues in food products. (25th April 2020) - Zhao, Jing; Meng, Zhaorui; Zhao, Zexin; Zhao, Longshan
Highlights: Green and efficient extraction method to analysis pesticides in food was proposed. UAE-DES coupled with MMWCNTs extraction method was established for the first time. Current method was green and sensitive to quantify pesticides in food matrices. The method was successfully applied to analysis of the pesticides in real samples. Abstract: A green and highly efficient ultrasound-assisted deep eutectic solvent extraction combined with functionalized magnetic multi-walled carbon nanotubes solid-phase extraction method for determination of seven pesticide residues in food products was developed. Various types of deep eutectic solvents (DESs) were screened for high extraction efficiencies and DES composing of proline and propylene glycol at 1:3 M ratio was selected as it exhibited highest yields. Extraction conditions were statistically optimized through response surface methodology using a Box-Behnken design. The established method was linear, precise, and accurate over the range of 0.1–50 μg mL −1 . Limit of detection and limit of quantification were in the range of 0.02–0.05 μg mL −1 and 0.05–0.10 μg mL −1, respectively. The mean recoveries for pesticides ranged from 76.09 to 97.96% with relative standard deviation of 0.13–10.05%. The proposed method was successfully applied to analysis of the pesticides in real samples, which is a potentially promising technique for food matrix.